Impact of COVID-19 on disease-specific mortality, healthcare resource utilization, and disease burden across a population over 1 billion in 31 countries: an interrupted time-series analysisResearch in context - Kyungseon Choi; Minseol Jang; Siin Kim; Sang Jun Park; Hae Sun Suh (EClinicalMedicine, 2025)
Summary: Background: The COVID-19 pandemic disrupted global health and affected chronic disease management. This study quantified the impact of the pandemic on disease-specific measures of health dynamics, such as mortality rates, healthcare resource utilization (HRU), and disease burden. Methods: An interrupted time-series analysis was performed by examining temporal trends across disease categories over two periods: pre-pandemic and pandemic (after January 2020). Monthly mortality data were collected from 31 countries, while monthly HRU and disease burden data were collected from South Korea. We defined primary outcomes as disease-specific mortality rate, number of patients, outpatient visits, days of hospitalization, disease burden, and per capita cost. We used a generalized least squares model with AR (1) residuals and an automated SARIMA model and Benjamini–Hochberg-adjusted q-values were applied for statistical significance (q < 0.05). Findings: A significant increase in disease-specific mortality was observed across multiple countries, with circulatory diseases showing the most widespread rise. HRU declined across most disease categories, including reductions in patient numbers, outpatient visits, and hospital stays; however, patient number showed sustained increase in neoplasm and mental disorder. Although changes in total direct medical costs varied by disease, per capita costs initially increased despite a decrease in the number of patients. Interpretation: The pandemic led to increased mortality and disease burden with limited access to healthcare services. Establishing resilient healthcare systems and appropriate public health policies are key to ensure continuity of care during national crises. Funding: Ministry of Food and Drug Safety of Korea; National Research Foundation of Korea; Korean Government; Korea Environment Industry & Technology Institute.